Propuesta De Diseño Arquitectónico De Espacios Agro Productivos Sostenibles En Las Comunidades Arroceras Del Juncal Huila (2021)
The following work is developed in the extension of the Juncal, municipality of Palermo, a territory which has been the scene of high concentration and growth of rice and paddy activities, lending itself to the development of a research work that allows to analyze in depth the current problems that plague the rice farming sector in general, and from this analysis, a research question is developed that allows to direct the project, being this the one of: How to design sustainable agro-productive spaces that guarantee stability and mitigate the problems that small rice producers of Juncal - Huila presently have? With this established, the project seeks to provide a practical solution to the elements found today, developing alternatives and exposing highly relevant characters from the analysis and referential interventions that allow to conclude with a specific architectonic alternative, taking into account theoretical and conceptual elements for the improvement of the rice culture of the territory.